Quality of Service and Client Satisfaction of the Department of Foreign Affairs - Butuan, Caraga Region - Zaportiza-Corvera, Rhodarora Galido (JPAIR Multidisciplinary Research, 2017)
The quality of service determines client satisfaction. The study aimed to determine the quality of service and client satisfaction of the Department of Foreign Affairs- Butuan. There were 221 or more than 70% respondents used in the study. There were those who personally claimed their passport in the releasing section within the five-working-day office transaction. In this study, the descriptive research was used. The researcher then employed the probability sampling design. The study revealed that there were more females than males who availed of the services of the Department of Foreign Affairs- Butuan with the intention to travel to a foreign land to work as contract workers. The study also disclosed the extent of service as to the issuance of Passport was rated Very Satisfactory by the respondents while some of them had an inadequate knowledge and awareness of the services on the Assistance to Nationals. The quality of service was all rated Very Satisfactory so as the level of client satisfaction in terms of frontline behavior, accessibility and efficiency in the delivery of service. There was a highly significant relationship between the services on issuance of passport and the level of satisfaction of client. An increase in the services on issuance of passport by the Department of Foreign Affairs-Butuan resulted to the increase in the level of client satisfaction.
Keywords: Management; service quality; client satisfaction; Department of Foreign Affairs; descriptive design; Caraga; Philippines